2011 IEEE International Conference on Communications (ICC) 2011
DOI: 10.1109/icc.2011.5962785
|View full text |Cite
|
Sign up to set email alerts
|

A Seamless Quality-Driven Multi-Hop Data Delivery Scheme for Video Streaming in Urban VANET Scenarios

Abstract: Abstract-In this paper, we propose an integrated networklayer scheme for seamless delivery of video packets in VANET. First, we introduce a new quality-driven routing scheme for delivering video streams from a fixed network to a destination vehicle via multi-hop communications. The routing scheme aims to optimize the visual quality of the transmitted video frames by minimizing the distortion, the start-up delay, and the frequency of the streaming freezes. We then propose an efficient network mobility managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 11 publications
(12 reference statements)
0
9
0
Order By: Relevance
“…Results showed that within certain distance, IEEE802.11a and g based VANET are able to achieve better stability good put, while IEEE802.11b based VANET is better suited for long distance communication. On the other hand, a novel adaptation of PMIPv6 for multi-hop VANET scenarios is introduced in [44], to ensure efficient network mobility management. This shows the importance of network selection in VANET towards determining the transmission efficiency.…”
Section: Network Selectionmentioning
confidence: 99%
“…Results showed that within certain distance, IEEE802.11a and g based VANET are able to achieve better stability good put, while IEEE802.11b based VANET is better suited for long distance communication. On the other hand, a novel adaptation of PMIPv6 for multi-hop VANET scenarios is introduced in [44], to ensure efficient network mobility management. This shows the importance of network selection in VANET towards determining the transmission efficiency.…”
Section: Network Selectionmentioning
confidence: 99%
“…Most of the existing works on mobility management [16,25] focus on layer-3 schemes to extend the support of Mobile IP (MIP) to vehicular networks but not on the handover decision parameters. The handover decision is mostly based on either of the RSSI [14] or LET [30,15] metric. To efficiently support the dissemination of high resolution and delay sensitive telescreen content in urban areas, we propose a handover decision mechanism based on both the RSSI and LET parameters to select a stable link and avoid unnecessary handovers.…”
Section: Vehicular Network and Handover Decisionmentioning
confidence: 99%
“…Utilizing VANET technology enables variety of applications for improving passengers safety, alleviating traffic flow, reducing pollution and enabling in-vehicle entertainment for passengers [1][2][3]. In addition, vehicles could use the available network infrastructures in a city to access Internet [4].…”
Section: Introductionmentioning
confidence: 99%